STUDENTS’ PERCEPTION OF QUIZIZZ USES AS ENGLISH LEARNING MEDIA - Fitriana Kartika Sari; Elsara Khairun Nisa; M. Erwin Dwi Listyanto; Khalid Iskandar (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
The development of Information Communication and Technology (ICT) considerably influences all aspects of human life, including education. With the development of ICT, the lecturer must also be able to follow its development by adapting ICT into the learning process, for example in learning media. In Indonesia, the application of ICT as a learning media is the newest trend. The research in this paper aims to discover the students’ perceptions regarding the use of Quizizz as English learning media. The research design is survey research. The research subject involved 15 Agribusiness students at Universitas Muhadi Setiabudi. The questionnaire in the form of Google Forms is used to process the data collection and subsequently analyzed by using the Likert Scale. The research result indicates that students’ perception of the use of Quizizz is highly positive with a questionnaire result of 750. It means they strongly agree that Quizizz is highly useful and suitable to use as a learning medium in English subjects. In addition, they agree that Quizizz can create a fun English learning atmosphere.